Clinical and biochemical profiles suggest fibromuscular dysplasia is a systemic disease with altered TGF‐β expression and connective tissue features. Issue 8 (14th April 2014) - Ganesh, Santhi K.; Morissette, Rachel; Xu, Zhi; Schoenhoff, Florian; Griswold, Benjamin F.; Yang, Jiandong; Tong, Lan; Yang, Min‐Lee; Hunker, Kristina; Sloper, Leslie; Kuo, Shinie; Raza, Rafi; et al.
Abstract : Fibromuscular dysplasia (FMD) is a rare, nonatherosclerotic arterial disease for which the molecular basis is unknown. We comprehensively studied 47 subjects with FMD, including physical examination, spine magnetic resonance imaging, bone densitometry, and brain magnetic resonance angiography. Inflammatory biomarkers in plasma and transforming growth factor β (TGF‐β) cytokines in patient‐derived dermal fibroblasts were measured by ELISA. Arterial pathology other than medial fibrodysplasia with multifocal stenosis included cerebral aneurysm, found in 12.8% of subjects. Extra‐arterial pathology included low bone density ( P <0.001); early onset degenerative spine disease (95.7%); increased incidence of Chiari I malformation (6.4%) and dural ectasia (42.6%); and physical examination findings of a mild connective tissue dysplasia (95.7%). Screening for mutations causing known genetically mediated arteriopathies was unrevealing. We found elevated plasma TGF‐β1 ( P =0.009), TGF‐β2 (P = 0.004) and additional inflammatory markers, and increased TGF‐β1 ( P =0.0009) and TGF‐β2 ( P =0.0001) secretion in dermal fibroblast cell lines from subjects with FMD compared to age‐ and gender‐matched controls. Detailed phenotyping of patients with FMD allowed us to demonstrate that FMD is a systemic disease with alterations in common with the spectrum of genetic syndromes that involve altered TGF‐β signaling and offers TGF‐β as a marker of FMD.—Ganesh, S. K., Morissette, R., Xu, Z., Schoenhoff, F., Griswold, B. F., Yang, J., Tong, L., Yang, M.‐L., Hunker, K., Sloper, L., Kuo, S., Raza, R., Milewicz, D. M., Francomano, C. A., Dietz, H. C., Van Eyk, J., McDonnell, N. B. Clinical and biochemical profiles suggest fibromuscular dysplasia is a systemic disease with altered TGF‐β expression and connective tissue features. FASEB J. 28, 3313–3324 (2014). www.fasebj.org